Разложите на множители: 2(3-b)+5(b-3)^2

Разложите на множители: 2(3-b)+5(b-3)^2
Гость
Ответ(ы) на вопрос:
Гость
2(3 - b) + 5(b - 3)² = 6 - 2b + 5(b² - 6b +9) = 6 - 2b + 5b² - 30b + 45 =                            = 5b² - 32b +51          D = 1024 - 1020 = 4                                                             b₁ = (-b + √D)/2a = (32 + 2)/10 = 3,4                                                             b₂ = (-b - √D)/2a = (32 - 2)/10 = 3 5b² - 32b +51 = 5(b - 3,4)(b - 3) = (5b - 17)(b - 3)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы